Water Quality Of Lake Toba By Space And Time Based On Environmental Physics, Chemical Factors And Community Phytoplankton - Ika Rosenta Purba; Nurhayati Nurhayati (Green Publisher Indonesia, 2022)
The purpose of this study was to analyze the water quality of Toba Lake based on the physics-chemical properties of the waters, the phytoplankton community, and the relationship between the physico-chemical factors of the water and the phytoplankton community according to space and time. This research was conducted during two seasons, Dry season (April, May, July) and Rainy season (October, November and December), and was conducted at four stations, namely around the floating net cage area, around the pier, around the agricultural area, and the control area near the waterfall. Data analysis was performed using the SAS 913 program and the Duncan Multiple Range Test (DMRT). The results of the analysis of water physics-chemical factors by space and time showed the quality of the waters in each station is still relatively good, except for floating net cages that have lower oxygen solubility.Data on chemical physics factors that affect phytoplankton in the waters of Lake Toba based on space, namely the temperature factor is in the range of 26.41 °C - 26.70 °C, light penetration in the range of 3.44 m - 5.10 m, degree of acidity (pH) in the range of 7.89 – 8.27, oxygen solubility (DO) in the range of 4 mg/L- 6.79 mg/L, biochemical oxygen requirements (BOD5) in the range of 0.69 mg/L - 0.95 mg/L, conductivity is in the range of 97.39 μS/cm - 164.59 μS/cm, total dissolved solids (TDS) are in the range of 91.48 mg/L - 98.1 1 mg/L, total nitrate is in the range of 2.14 mg/L - 3.95 mg/L, phosphate content (PO4) is in the range of 0.009 mg/L - 0.013 mg/L.